QUALIDADE DOS DADOS DO ÍNDICE DE BULBO ÚMIDOTERMÔMETRO DE GLOBO (IBUTG) COLETADOS COM INSTRUMENTOS AUTOMÁTICOS EM AMBIENTE EXTERNO - Amorim, Adriana; Labaki, Lucila; Maia, Paulo; Barros, Thais Maria Santiago; Monteiro, Luiz Roberto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Excessive environmental heat can cause illnesses and deaths of construction workers. Environmental assessment specifies the preventive measures to avoid overload and its consequences on health. The most accepted method for occupational exposure is the Wet Bulb Globe Temperature Index (WBGT) comparison with permissible exposure limits. The traditional method is considered more accurate, by measuring natural wet-bulb temperature (Twb), dry-bulb temperature (Tdb) and black-globe temperature (Tg), from their respective mercury thermometers. Nowadays it is being replaced by automatic dataloggers that capture and record measured data. The aim of this work is to evaluate the quality of the so obtained data, by comparing them to those from mercury thermometers, as well as to develop more accurate mathematical algorithms for acquiring Twb, Tdb and Tg from measurements through QuestTemp36TM electronic equipment. Data from the two sets of equipment were collected on concrete slabs and grass, during six days in March 2017. The results for the WBGT with the two systems were tested statistically through linear regressions, which resulted in determination -values < 0.0001. These results show that it is possible to improve the accuracy of the measurements performed with automatic instruments through equations of the linear regression method.